Facilitating LGBT medical, health and social care content in higher education teaching - Davy, Zowie; Amsler, Sarah; Duncombe, Karen (Hipatia Press, 2015)
ncreasingly, Lesbian, Gay, Bisexual, and Transgender (LGBT) health care is becoming an important quality assurance feature of primary, secondary and tertiary healthcare in Britain. While acknowledging these very positive developments, teaching LGBT curricula content is contingent upon having educators understand the complexity of LGBT lives. The study adopted a qualitative mixed method approach. The study investigated how and in what ways barriers and facilitators of providing LGBT medical, health and social care curricula content figure in the accreditation policies and within undergraduate and postgraduate medical and healthcare teaching. This paper illustrates opposing views about curricula inclusion. The evidence presented suggests that LGBT content teaching is often challenged at various points in its delivery. In this respect, we will focus on a number of resistances that sometimes prevents teachers from engaging with and providing the complexities of LGBT curricula content. These include the lack of collegiate, colleague and student cooperation. By investing some time on these often neglected areas of resistance, the difficulties and good practice met by educators will be explored. This focus will make visible how to support medical, health and social care students become aware and confident in tackling contemporaneous health issues for LGBT patients.